Townhouses and more - Kramer, Sibylle ([S.l.] : Verlagshaus Braun, 2008)
Inner cities are experiencing a newed boom, the demand for 21st century living spaces in today?s renaissance of urban centralization is on the rise. So for the past few years, many architects have been rediscovering and creatively reinterpreting the aeste.